Nilai-Nilai dan Pesan-Pesan Moral Tarling Menurut Perspektif Pelaku Kesenian Tarling Cirebon (Sebuah Studi Psikologi Budaya) - , Rijal Abdillah, Prof. Drs. Koentjoro, MBSc, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purposes of this research were to analyze deeply the values and moral messages of Tarling in subject perspective of Tarling-Cirebon Art Performers and performers internalization of the values and moral messages Tarling. The purpose of this research aimed to answer the research question, how the values and moral messages according to the subject perspective of Tarling Cirebon art performers and performers internalization of the values and moral messages Tarling? This research is based on an qualitative study. Subjects perspective of values and moral messages in Tarling Art were gathered through observations, interviews, and documentation. The analyzing of internalization process of values and moral messages was inspired by ethnography. The result of this study indicate that the values of tarling obtained are empathy of subjects in tarling, covering âdandanggulaâ song of Sunan Kalijaga, ângalap berkahâ or seeking blessing, âa plate of riceâ philosophy, âapa jare wong tua ngagem ngageme wong rumah tanggaâ or happy household, and âpayun geneng sabonana payun geneng sabot enteng lakonanaâ or mutual cooperation. That there is explicitly moral messages that absorbed are âingsun titip tajug lan fakir miskinâ philosophy of Sunan Gunung Djati, conversation in polite language such as âpuntenâ expression, âsabasitaâ or âunggah-ungguhâ behavior, âpamaliâ or do behavior charily, âyen wis mlatar gage elingâ philosophy of tarling, and âsaweranâ tradition. The internalization process of values and moral messages performers obtained through five stages based on an taxonomy of educational objectives from Bloom et.al, (1970). The first is an receiving. The second is an responding. The third is that the valuing. The fourth is that organization values. The Last internalization process of values and moral messages are the characterization. Keywords : Values, Moral, Tarling Cirebon Art, Cultural Psychology